İnsan sağlığı ve çevre kirliliği açısından Kırklareli ilinin fon radyasyonunun belirlenmesi ve haritalandırılması - Taşkın, Halim (My University, 2006)
Bu çalışmada Kırklareli iline ait toprak ve su örneklerinin radyoaktivite konsantrasyonları, gama ışınlama doz hızları ve ev içi radon konsantrasyonlarının tespit edilmesi amaçlanmıştır. Araştırma sahası Kırklareli il sınırları içindeki 8 ilçe 20 belde ve 177 köy olmak üzere tüm il genelini kapsamıştır. İl genelindeki tüm kaynak ve şebeke suları (220 adet) araştırma kapsamına alınmıştır. Direkt gama ölçümleri ve toprak örnekleri için alan örnekleme yöntemi kullanılmıştır. Evlerde radon ölçümleri için ise haneler, küme örnekleme yöntemiyle belirlenmiştir. İçme suyu örneklerinin toplam alfa ve beta aktiviteleri, Berthold marka, gaz-akışlı LB770- PC 10 kanallı düşük seviyeli orantılı sayıcı kullanılarak, ev içi radon konsantrasyonları, pasif CR–39 nükleer iz detektörleri kullanılarak, gama ışınlama doz hızları Eberline Smart, taşınabilir bir sintilasyon detektörü kullanılarak, toprak örneklerinin radyonüklid konsantrasyonları da Gama Spektrometri Sistemi kullanılarak gerçekleştirilmiştir. 220 su ve 177 adet toprak örneği alınmış, 315 evde radon ve 230 yerde direkt gama ölçümleri yapılmıştır. Ortalama alfa aktivitesi 0,0405 ± 0,0382 Bq/ m3 olarak bulunmuştur. 220 örnekten 12 (% 5,5) tanesinde alfa aktivitesi sınır değerlerin üzerinde çıkmıştır. İl geneli için ev içi ortalama radon konsantrasyonu 71,01 ± 39,85 Bq/ m3 olarak bulunmuştur. Değerlendirilen detektörlerin tamamı, ülkemizin kapalı ortamlar için müsaade ettiği sınır değer olan 400Bq/ m3’lük konsantrasyon değerinin altında çıkmıştır. Ancak 301 detektörden 50 (%16,6) sindeki radon konsantrasyonu DSÖ’nün belirlediği sınır değer olan 100 Bq/ m3’ten yüksek çıkmıştır. Bina tipi ve tavan yapı malzemesinin radon konsantrasyonunda etkisi olduğu tespit edilmiştir (p<0,05). İl geneli için gama ışınlama doz hızları ortalama 135,086 ± 38,648 nGy/ saat olarak ölçülmüştür. Toprak örneklerindeki radyoizotop aktivite konsantrasyonları sırayla 226Ra’da ortalama 36,504±17,540 Bq/ kg, 238U’de ortalama 25,428±10,892 Bq/ kg, 232Th’de ortalama 39,864±18,382 Bq/ kg, 40K’da ortalama 666,98±281,01 Bq/ kg, ve 137Cs ‘de ortalama 7,954±5,349 Bq/ kg, olarak bulunmuştur. Her ne kadar il ve ilçe ortalamaları bazında sonuçlar DSÖ ve diğer uluslararası kuruluşların belirlediği limit değerlerin altında çıkmış ise de, ölçüm ve analiz sonuçları tek tek değerlendirildiğinde bu limit değerlerin az da olsa aşıldığı görülmüştür. Limit değerlerin üzerinde çıkan içme sularında radyoaktivitenin mevsimsel değişimi takip edilmeli ve radon konsantrasyonu yüksek çıkan evlerde evlerin düzenli havalandırılması konusunda eğitim çalışmaları yapılmalıdır. Ülkemizde radyoaktif kaynakların yeterince bilinmemesi, insan sağlığının korunması açısından radyolojik risk tahminini güçleştirdiği için tüm illerde benzer çalışmalar yapılarak doğal fon radyasyonlarının belirlenmesi önemlidir. radyoaktivite, Gama doz hızı, Toplam alfa ve beta, Ev içi radon konsantrasyonu, Yıllık etkin doz

THE DETERMİNATİON AND MAPPİNG OF THE BACKGROUND RADİATİON KIRKLARELİ, İN TERMS OF ENVİRONMENT HUMAN AND HEALTH The aim of this study was to determine the natural radioactivity concentration in soil and water samples and to measure environmental outdoor gamma dose rate and indoor radon concentration in Kırklareli The study contains total area of Kırklareli city. Samples was taken 8 towns, 20 districts and 177 villages in and around of city center. 220 water samples was taken from drinking water sources and tap water in houses. To determine environmental outdoor gamma dose rate and radionuclides concentration in soil samples was used by the method of area sampling. Indoor radon measurements was determined by the method of cluster sampling. Gross alpha and gross beta radioactivity measurements in water samples was determined by using Berdhold mark and LB770-PC model 10 channel low level proportional counter system. Indoor radon concentrations was detected by using the passive CR-39 nuclear track detector. Outdoor gamma dose rates was measured with Eberline Smart mark and SP6 model pilastic sintilator detector. Radionuclides concentration in soil samples was measured by using Canberra mark HP Germanium detector. Avarage gross alfa activity in water samples was measured as with the medium, minimum and maximum values of 0,0405 ± 0,0382 Bq/ m3, 0,0026 Bq/ m3, 0,0311 Bq/ m3 0,4461 Bq/ m3 respectively. The alpha activity in the 208 (% 94,5) samples of 220 in total, has proved to be under the acceptable limits for drinking waters which was determined by WHO. However, in 12 samples (%4,5) the alpha activity turned out to be beyond this limit. Especially, the radioactivity of the water sample which was collected from a fountain in the village Yoğuntaş was 4 times higher than the limit value. The avarage indoor radon concentration is 71,01 ± 39,85 Bq/ m3, with the medium, minimum and maximum values of 61 Bq/ m3, and 325 Bq/ m3 respectively. All the detectors evaluated, are above the acceptable indoor radon limit for Turkey, which is 400Bq/ m3. However, the radon concentration level in 50 (%16,6) houses out of 301 was beyond the limit which was determined by WHO as 100Bq/ m3. The avarage outdoor gamma dose rate was measured as 135,086 ± 38,648 nGy/ hour, with the medium, minimum and maximum values of 131 nGy/ hour, 32 nGy/ hour and 325 nGy/ hour respectively. The avarage radioisotop concentrations were foud out as 36,504±17,540 Bq/ kg, in 226Ra 25,428±10,892 Bq/ kg, in 238U, 39,864±18,382 Bq/ kg in 232Th, 666,98±281,01 Bq/ kg, in 40K and 7,954±5,349 Bq/ kg in 137Cs respectively. In general, gross alpha and gross beta radioactivity levels in drinking water samples, indoor radon concentrations in houses, outdoor gamma radiation dose rates and radionuclide concentrations in soil samples was found the acceptable limits determined by the international organisations ICRP and WHO. However, some gross alpha radioactivity results in 12 district waters was found above limits. Especially, the gross alpha radioactivity in Yoğuntaş vilage water was determined four times higher than the acceptable limit. Indoor radon concentrations in 50 houses was found above the international average level. Outdoor gamma radiation dose rates varied considerible depending on the geological characterictis. K-40, Th-232 and Ra-226 radiaoactivity concentrations in some region’s soil samples was found higher than others and the outdoor gamma radiation dose rates in the same places was also found higher than others. In addition, the equilibrium dose rates which stem from gamma dose rate and radon inhaletion were calculated and discussed in terms of radiation protection and safety. Natural radioactivity, Gamma dose rate, Gross alpha and beta, İndoor radon concentration, Annual effective dose
Keywords: Çevre Kirliliği; Doğal Radyoaktivite; Ev İçi Radon Konsantrasyonu; Gama Doz Hızı